IMPLEMENTASI PENGEMBANGAN ORGANISASI DALAM PERSPEKTIF GOOD CORPORATE GOVERNANCE PT. POS INDONESIA (Studi Kasus Pada PT. Pos Indonesia Regional VI Semarang) - Mahfuzh, Alfian; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to identify the understanding and implementation of Good Corporate Governance in employees of PT. Pos Indonesia (Transparency, Accountability, Responsibility, Independency, Fairness). In this research, the method used is qualitative method. This research was conducted at PT. Pos Indonesia Regional VI, Central Java-Jogjakarta. The research subjects are employees of PT. Pos Indonesia Regional VI, Central Java-Jogjakarta who occupy managerial positions and have worked in a period of more than 10 years as the main focus. Data collection is done by interview, observation and documentation. The results showed that (1) Employees understanding of GCG conducted at PT. Pos Indonesia Regional VI, Central Java-Jogjakarta has been very good. (2) GCG implementation conducted by employees of PT.Pos Indonesia Regional VI Central Java DIY has been applied optimally in accordance with rules and guidelines.